Serum interferon gamma level predicts recurrence in hepatocellular carcinoma patients after curative treatments. Issue 12 (25th June 2013) - Lee, I‐Cheng; Huang, Yi‐Hsiang; Chau, Gar‐Yang; Huo, Teh‐Ia; Su, Chien‐Wei; Wu, Jaw‐Ching; Lin, Han‐Chieh
<x xml:space="preserve">Abstract</x> Host immunity may have important role in the prognosis of hepatocellular carcinoma (HCC). The aim of this study was to evaluate the correlation between circulating immune regulators and clinical outcome in patients with HCC. Sixty‐three HCC patients were prospectively enrolled. Serum levels of interleukin‐10 (IL‐10), transforming growth factor‐beta (TGF‐β), interferon‐gamma (IFN‐γ) and interferon gamma‐inducible protein 10 (IP‐10) were measured, as well as the prevalence of regulatory T cells (Treg), NK+ T cells, invariant natural killer T cells (iNKT), programmed cell death‐1 (PD‐1)+CD8+ T cells, T helper 17 cells (Th17), CD69+ and CD45RO+ T cells in peripheral blood mononuclear cells (PBMC). Correlation between these immune regulators and clinical outcome were analyzed. A low serum IFN‐γ level (<50 pg/mL) was significantly associated tumor stage (BCLC stage B: 61.25% vs. stage A: 25%, p = 0.010) and tumor size (>5 cm: 53.8% vs. <5 cm: 25%, p = 0.047). Recurrence‐free survival was evaluated in 48 patients receiving curative treatment of HCC. By multivariate analysis, BCLC stage [hazard ratio (HR) = 32.180, p < 0.001], tumor size (HR = 15.373, p = 0.005), AST (HR = 3.796, p = 0.011) and IFN‐γ (HR = 0.354, p = 0.018) levels were independent factors associated with recurrence‐free survival. In conclusion, serum IFN‐γ level correlates with tumor stage and tumor size in HCC patients. Patients with lower baseline IFN‐γ levels have a higher risk of tumor recurrence after curative treatment. IFN‐γ may reflect host anti‐tumor immunity and may be a potential marker of HCC recurrence after curative treatment.